2009
DOI: 10.1002/app.31061
|View full text |Cite
|
Sign up to set email alerts
|

Novel method of synthesizing poly(ether sulfone) membranes containing two solvents and a lithium chloride additive and their performance

Abstract: The influence of a lithium chloride (LiCl) additive on poly(ether sulfone) (PES) membranes was investigated. A microwave technique was used to prepare membrane dope solutions, and two different types of solvent systems were used: single-solvent (SS) and double-solvent (DS) systems. In the SS system, PES was dissolved in N,N-dimethylformamide (DMF), and In the DS system, PES was dissolved in DMF and acetone. In the DS system, the control ratio of DMF to acetone was kept at 3.47, and the concentration of LiCl in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 46 publications
3
30
1
Order By: Relevance
“…However, higher amount of NaBr does not promote the hydrophilic properties as exhibited by its low flux rates probably owing to the formation of salt–solvent complexes which diffused out during the phase inversion process. Similar findings38 were also reported that LiCl and DMF formed salt–solvent complexes which resulted in hydration effect and caused swelling in the polymer gel 41…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…However, higher amount of NaBr does not promote the hydrophilic properties as exhibited by its low flux rates probably owing to the formation of salt–solvent complexes which diffused out during the phase inversion process. Similar findings38 were also reported that LiCl and DMF formed salt–solvent complexes which resulted in hydration effect and caused swelling in the polymer gel 41…”
Section: Resultssupporting
confidence: 83%
“…The permeation rates of commercially available spiral wound membranes can range from as low as 4.5L/m 2 h to as high as 53 L/m 2 h as listed in Table II. N‐1 membrane also exhibited higher PWP compared to membrane with highest PWP in the dual solvent system as reported in our previous study, which used LiCl as salt additives 38…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…5. These observations were believed to be associated with the change in the thermodynamic properties and phase inversion kinetics of the PES systems without and with the addition of an additive [20,31]. Hansen solubility parameter for each component in PES system is summarized in Table 3, from which the total solubility parameter difference can be derived (Table 4).…”
Section: Effect Of Non-solvent Additive On the Morphology Of The Dualmentioning
confidence: 99%